ANTITROMBOTIC ACTIVITY OF A NEW BENZIMIDAZOLE DERIVATIVE WITH A SPATIALLY DIFFICULT PHENOLIC SUBSTITUTE IN ITS STRUCTURE - Alexander A. Spasov; Aida F. Kucheryavenko; Ksenia A. Gaidukova; Maxim V. Chernikov; Olga N. Zhukovskaya (Фармация и фармакология (Пятигорск), 2020)
The aim of the study was to investigate antithrombogenic properties of compound RU-1144 with previously identified pronounced antiplatelet and antioxidant activities. The thrombosis induced by Ferric chloride (FeCl3) was carried out in rats’ carotid artery, in comparison with the known antiaggregant drugs - acetylsalicylic acid (ASA) and clopidogrel, as well as with the antioxidant preparation - ethylmethylhydroxypyridine succinate (EMHPS).Materials and methods. The antithrombotic activity of compound RU-1144 was studied on the model of the rats with carotid artery thrombosis, induced by the application of 50% ferric chloride (FeCl3), and the Global Thrombosis Test model (the Görög Thrombosis Test). The evaluation of this type of activity was carried out by prolonging the time of a blood clot formation. The studies of the compound RU-1144 effect on the bleeding time parameter were performed in mice. Acetylsalicylic acid, clopidogrel and EMHPS were used as reference drugs.Results. The antithrombotic effect of the RU-1144 substance revealed in the model of arterial thrombosis induced by the application of ferric chloride (FeCl3), exceeded that of both acetylsalicylic acid and clopidogrel by 3.5 times and that of EMHPS by 2.9 times. In the model of the in vitro Global Thrombosis Test (the Görög Thrombosis Test), compound RU-1144 reduced the thrombogenic potential of the blood equally with acetylsalicylic acid and clopidogrel. The assessment of “the bleeding time”, caused by the RU-1144 substance, showed that the prolongation of bleeding was twice as less pronounced than that caused by ASA and clopidogrel.Conclusion. The performed studies demonstrated a pronounced antithrombotic activity of compound RU-1144, which exceeded that of acetylsalicylic acid, clopidogrel and EMHPS, while the ability to prolong the bleeding time was reliably lower than that of reference drugs.Abbreviations: EMHPS-ethylmethylhydroxypyridine succinate; ASA - acetylsalicylic acid.